VID 2021
DOI: 10.1553/0x003d06d6
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Reproductive Intentions in Europe

Abstract: Aim of this paper is to investigate the effects of environmental conditions on human reproductive behavior in the highest industrialized countries. We discuss the hypothesis that individuals fearing for a foreseen unhealthy environment tend to delay or forgo childbearing, thus contributing to a reduced ecological footprint. The empirical analysis is based on the Eurobarometer survey carried out in the 27 EU countries in 2011. Multilevel ordinal regression models on additionally intended number of children are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…As a result of these concerns, most interviewees and some commentators felt selfish for having children. They saw the decision to go childfree as a safeguard against exposing unborn children to environmental risks (De Rose and Testa 2015a). Yet, despite these concerns, some participants believed they may have children, but not more than two; which is consistent with previous findings (Andrijevic and Striessnig 2017;Basten et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of these concerns, most interviewees and some commentators felt selfish for having children. They saw the decision to go childfree as a safeguard against exposing unborn children to environmental risks (De Rose and Testa 2015a). Yet, despite these concerns, some participants believed they may have children, but not more than two; which is consistent with previous findings (Andrijevic and Striessnig 2017;Basten et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…When using the data collected among college students or people who self-identify as concerned by environmental changes, the research found less positive attitudes toward having children (Arnocky et al , 2012; Davis et al , 2019; Schneider-Mayerson and Leong, 2020; Marks et al , 2021). Differently, studies that mobilize more representative samples do not find a correlation between environmental concerns and reproductive attitudes (De Rose and Testa, 2013).…”
Section: Theoretical and Conceptual Backgroundmentioning
confidence: 99%
“…Notwithstanding, another survey of 1000 European individuals of reproductive age found no correlation between environmental concerns and family planning measures 65 . In Nepal, one study indicated higher contraceptive use in relation to environmental degradation 66 and another associating higher pregnancy rates with greater land scarcity 67 . In sub‐Saharan Africa, empirical analysis of demographic health data revealed an association between increased temperature and decreased fertility preferences, but only among women in more rural areas 68 .…”
Section: Eco‐anxiety and Women's Healthmentioning
confidence: 99%